High-resolution nanostructural investigation of Zn4Sb 3 alloys - Gault, B.; Marquis, E.; Saxey, David; Hughes, G.; Mangelinck, D.; Toberer, E.; Snyder, G. (Elsevier, 2010)
Zinc antimonides exhibit high thermoelectric figures of merit and bear great potential for power generation. To advance the understanding of the structure-property relationship in these alloys, the microstructure of a nanocrystalline Zn4Sb3 alloy, containing 57.29 at.% Zn, was investigated by scanning electron microscopy and atom probe tomography. Chemical inhomogeneities were observed at grain boundaries. Within the grains the distribution of Zn shows large fluctuations inducing a complex microstructure made of Zn-rich and Sb-rich regions at a nanometer scale. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.